Ordovician corals of the Williston Basin periphery - Caramanica, Frank P. (UND Scholarly Commons, 1973)
Tabulate and rugose corals are described from the Ordovician Red River) Stony Mountain, and Stonewall Formations in southern Manitoba and the Ordovician Bighorn Formation in northern Wyoming. Fifty-four species, 12 of which are new, are distributed in 20 genera. The Flower Model of coral evolution, based on wall microstructure of colonial corals, is extended to include the septa! Microstructure of colonial and solitary corals. "Primitive" corals are characterized by non t-rabeculate walls and septa whereas "advanced" forms are characterizedby trabeculate walls and septa. "Mid-range" corals are those with intermediate stages of trabecular development in walls .and septa. Corals in the Red River Formation are primarily colonial, "primitive", and "mid-range," and are geographically widespread) ranging from New Mexico to Greenland in a northeast-southwest trending belt defining an Ordovician equatorial realm, but rarely occurring elsewhere in North America. Solitary corals in the Red River fauna were ancestral to those in the Stony Mountain fauna, but the colonial forms in the Red River Formation were not ancestral to those in the Stony Mountain. Corals in the Stony Mountain and Stonewall Formations in Manitoba and the faunas in the Bighorn Formation in northern Wyoming are younger, considerably more "advanced," and geographically more restricted than those in the Red River. The colonial corals are predominant in carbonate rocks whereas the solitary corals are most abundant in argillaceous carbonates and argillites, implying intolerance of the colonial forms for terrigenous elastics. The solitary forms were apparently not as efficient as the colonial corals in utilizing available energy under conditions of carbonate sedimentation. A paraconformity in the subsurface of northeastern North Dakota and diastems in the type section of the Fort Garry Member of the Red River Formation indicate that the cratonic platform east of the Williston Basin was e:x:posed for part or all of the time the evaporitic "upper Red River11 ...